The Influence of Personal Values and Cultural Beliefs on the Adoption of Sustainable Lifestyle - العلواني, أسماء شاكر عبود زبار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research explores the role of personal values and cultural beliefs in shaping and guiding individuals' behavior toward adopting sustainable lifestyles. The literature indicates that values such as responsibility, justice, and respect for nature are fundamental and primary drivers for embracing environmentally friendly practices. Cultural beliefs also play a pivotal role in either promoting or restricting such behavior through societal norms and cultural symbols. This research highlights the importance of integrating these factors into environmental policies and awareness programs to enhance the effectiveness of the transition toward sustainability. The research used a questionnaire consisting of a personal values scale, a cultural beliefs scale, and a sustainable behaviors scale. The data were analyzed using descriptive statistics, correlation coefficients, factor analysis, retrospective analysis, and regression analysis.